Secondary hyperaldosteronism and hypertension - Mijalković Miloš (Medicinski fakultet Priština, Društvo lekara Kosova i Metohije Srpskog lekarskog društva, 2021)
Introduction: Arterial hypertension is a major cardiovascular risk factor affecting about 10-40% of the adult population. Secondary endocrine hypertension most often results from excessive aldosterone secretion. Complications related to excessive aldosterone secretion include atrial fibrillation, myocardial infarction, myocardial fibrosis, left ventricular hypertrophy, stroke, and increased cardiovascular mortality. Case report: This report presents a hypotensive woman with hypertensive reactions, newly diagnosed unilateral hyperplasia of the left adrenal gland and secondary hyperaldosteronism. Due to good blood pressure and normalized electrolyte status as a result of antihypertensive drug therapy and absence of damage to target organs, surgical treatment of unilateral adrenal hyperplasia was postponed. Conclusion: In case of midlife and late-life hypertension, it is necessary to consider a cause in the patient's endocrine system. AUTHORS SUMMARY SRPSKI 2021; 50 (1,2) 51-54